Cantilever Bumi Sdn. Bhd. / Mohd Hakem Anas - Anas, Mohd Hakem (Faculty of Civil Engineering, 2019)
This industrial report consists of 4 chapters and that are introduction, training attended (weekly summary based on logbook), technical report and conclusion. For chapter 1 contain introduction, background of company, organizational structure and their functions, nature of business, products, market strength and conclusion. Chapter 2 is training attended. In this chapter consists introduction, exposure level and conclusion from the weekly summary based on logbook. While, chapter 3 consists technical report that obtain nature of work, problem encountered and how to overcome it and experience that have gained from the industrial training. For the last chapter, which has the conclusion, lesson learned, knowledge gained, suitability of organization, limitations and recommendations. In order to complete study, students have to undergo 8 weeks of industrial training from 15 July until 6 September 2019. Student need to choose their own company to undergo industrial training. Company that have been I choose is contractor company. During 8 weeks of training, trainee got opportunity to learn about engineering educational and how to supervise workers at site. Training schedule has been prepared by Q AQC engineer for the trainee to learn important task at company. Besides that, student also learn how to improve communication skills, learn to be discipline and punctual. Last but not least, the knowledge, skills and experience gain during the practical training is the best method in order to prepare student to expose to the real working environment and also to be a good and better engineer in future.